Dental professionals’ adaptation to COVID-19 transition in Malaysia - Rahman, Fazliny Abd.; Wern, Xin Ying; Ting, Ai Chee; Xian, Vanessa Tey Yu; Kamal, Zainab Shakirah Binti; Anuar, Anis Deanna Binti; Sonjaya, Donni; Zamzuri , Ahmad Termizi Bin (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: Coronavirus disease-2019 (COVID-19) has substantially impacted oral health services in Malaysia. The Prime Minister of Malaysia announced the “Transition to Endemic” phase of COVID-19. Although the World Health Organization issued provisional guidelines to address considerations for essential oral health services during the pandemic and endemic phases of COVID-19, there are limited studies on dental professionals’ knowledge, attitudes, and perceptions regarding COVID-19. Purpose: To investigate the attitudes, perceptions, and preparedness of dental professionals in Malaysia during the transition from the pandemic to the endemic phase of COVID-19. Methods: This study was conducted among dental professionals practicing in Malaysia, either in the private or public sector. A cross-sectional online survey of 151 dentists was conducted between December 1, 2022, and January 13, 2023. A questionnaire was disseminated via Google Forms. The data were analyzed using IBM SPSS for Windows, v. 22.0. Descriptive statistics and the chi-square test were used, with p < 0.05 considered significant. Results: The response rate was 100%. The majority of participants displayed a positive attitude toward the transition. Most respondents reported continuing to implement some general standard operating procedures in their dental practices. This study provides insights into the preparedness of dental practitioners in Malaysia for the transition from the COVID-19 pandemic to the endemic phase. Conclusions: The participants demonstrated a positive attitude and mental preparedness for the transition from pandemic to endemic, though some anticipated impacts on clinical practices during the post-lockdown period. This reflects an overall optimistic outlook among dental practitioners during this transition.